Cytogenetic biomonitoring of road tunnel construction workers: buccal micronucleus cytome assay - Villarini, M.; Guerrera, E.; Vannini, S.; Dominici, L.; Gianfredi, V.; Fatigoni, C.; Acito, M.; Moretti, M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Tunnel construction workers are exposed to complex mixtures of toxic agents, some of which are known to be genotoxic. The aim of this study was to evaluate the genotoxic risk in this occupational setting by comparing tunnel workers with a control group for frequencies of nuclear aberrations in oral exfoliated cells. Methods. To evaluate the genotoxic effects of tunnel air pollutants, we conducted a cross-sectional, molecular epidemiological study (35 tunnel workers and 35 healthy controls) using the buccal micronucleus cytome assay. A questionnaire was administered to obtain information about demographic variables, lifestyle, dietary habits, anthropometric data, and occupational history. Buccal mucosa cells were collected by scraping the buccal mucosa with a small-headed toothbrush. Coded slides were examined blind by trained scorers for micronuclei (MN), nuclear buds (NBUD), and other nuclear abnormalities. Results. Road tunnel construction workers revealed higher frequencies of cells with genotoxic damage (i.e., MN and NBUD). MN and NBUD resulted to be Poisson distributed and counts of these genotoxicity biomarkers were then analysed by Poisson regression. The frequency ratio (FR) for MN was 1.31 (95% CI: 0.84-2.04), with an increase in the exposed subjects; this finding, though indicating a higher genotoxic risk in the exposed subjects, did not reach statistical significance. On the other hand, the FR for NBUD was 3.49 (95% CI: 1.86-6.56), with a statistically significant increased risk of chromosomal damage. Even the frequencies of binucleated cells (a marker of cell proliferation) and pyknotic cells (a cell death biomarker) were significantly higher in tunnel workers. Conclusions. Our observations provide further knowledge and understanding of the occupational hazards of tunnel workers and confirm the complexity of effects (cytotoxic and genotoxic) probably induced by fumes and dust produced in underground operations.